2020
DOI: 10.7759/cureus.10851
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils to Lymphocyte Ratio: Earliest and Efficacious Markers of Sepsis

Abstract: Background Neutrophil to lymphocyte ratio (NLR) can be easily calculated from the white cell differential count and is considered an auspicious marker for predicting different diseases, including sepsis. In this study, we aimed to compare the efficacy of NLR as a sepsis marker by comparing it with other markers of sepsis, such as Creactive protein (CRP), procalcitonin, and the Sequential Organ Failure Assessment (SOFA) score. Methods A cross-sectional analytical study was conducted at the Aga Khan University H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
2
19
0
3
Order By: Relevance
“…In addition, there was statistically significantly higher proportion of CLD, MAP ≤ 50 mmHg, serum creatinine > 2.2 mg/dl, GCS <13, serum albumin ≤ 2.97 g/dL, serum bilirubin > 1.4 mg/dL, INR > 1.3, serum sodium ≤ 131 mEq/L, NLR > 10, CRP >12, APACHE II score > 19, SOFA score > 3 in non-survivors vs survivors. This came in the same line with Rehman and his colleagues (15) , who have demonstrated that the NLR showed significant associations with all the tested lab parameters of sepsis, such as CRP (p = 0.02), procalcitonin (p=0.01), and SOFA score (p=0.01). Values when analyzed according to culture-positive showed higher values in culturepositive samples but were not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, there was statistically significantly higher proportion of CLD, MAP ≤ 50 mmHg, serum creatinine > 2.2 mg/dl, GCS <13, serum albumin ≤ 2.97 g/dL, serum bilirubin > 1.4 mg/dL, INR > 1.3, serum sodium ≤ 131 mEq/L, NLR > 10, CRP >12, APACHE II score > 19, SOFA score > 3 in non-survivors vs survivors. This came in the same line with Rehman and his colleagues (15) , who have demonstrated that the NLR showed significant associations with all the tested lab parameters of sepsis, such as CRP (p = 0.02), procalcitonin (p=0.01), and SOFA score (p=0.01). Values when analyzed according to culture-positive showed higher values in culturepositive samples but were not statistically significant.…”
Section: Discussionsupporting
confidence: 86%
“…An elevated NLR likely represents dysregulation of the immune system reflecting an increased innate and attenuated adaptive immune response (8, 50). In addition to playing a role in ICH and stroke (26, 51) an elevated NLR has been linked to outcomes in patients with cancer, myocardial infarction, and sepsis (31,(52)(53)(54)(55)(56). Neutrophils infiltrate the cerebral vasculature within 10 min after SAH, and reduction of neutrophil levels or activity improves vascular integrity and outcomes in animal models (14, 57).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in NLR are indicative of the balance between neutrophil and lymphocyte counts. Several authors showed that NLR is an early biomarker of sepsis, regardless of the source of sepsis, and correlates with sepsis severity scores, such as The Acute Physiology and Chronic Health Evaluation II (APACHE II) score and SOFA score [100][101][102][103][104][105]. Noteworthy, NLR increases rapidly following infection.…”
Section: Neutrophil-to-lymphocyte Ratiomentioning
confidence: 99%